Characterization and identification of novel anti-inflammatory peptides from Baijiao sea bass (Lateolabrax maculatus). (July 2021) - Chen, Jiali; Bai, Weibin; Cai, Dongbao; Yu, Zhiling; Xu, Baojun
Abstract: Sea bass ( Lateolabrax maculatus ) is one of economically important cultured fish species in China. Our previous study indicated that sea bass possessed anti-inflammation effects. However, the potential active components of sea bass remain unclear. The objective of the current study is to characterize the active components from sea bass. Ultrafiltration and size-exclusion chromatography were applied for activity-guided isolation. Bioactive fractions were further characterized upon TEM, FTIR, hydrodynamic diameter, ζ-potential, and LC-QE–HF–MS. Results indicated that fraction F1 (<10 kDa) possessed the strongest anti-inflammatory activity. Further characterization revealed that fraction F1 were uniform nanoparticles with negative charge and stability. Moreover, DAPAPPSQLEHIRAA and AADGPMKGILGY were the identified peptides in fraction F1 with the strongest anti-inflammatory capacity. It has potential to be developed as nutraceutical products. The present findings provided the chemical basis for the identification of active constituents in sea bass in managing inflammation-associated conditions. Graphical abstract: Image 1 Highlights: Fraction F1 (Mw < 10 kDa) was identified as the active constituent in sea bass. Uniform nanoparticles with negative charge were found in active fraction F1. anti-inflammatory activity-guided isolation was done by ultrafiltration and SEC. Anti-inflammatory peptides were identified as DAPAPPSQLEHIRAA and AADGPMKGILGY.